Cone beam computed tomography guided surgical stent: A preimplant planning procedure, a pilot study - Kritika Saxena; Bharat M Mody; Akshay Rathore (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of the present study was to evaluate the efficacy of cone-beam computed tomography (CBCT)-based radiologic stent in guidance for preimplant placement procedures. Setting and Design: This study was a pilot study conducted among 5 patients who presented for dental implants and attending the department of Oral Medicine and Radiology, ITS Dental College, Muradnagar for CBCT volumetric scans. Materials and Methods: The dimensions of bone available for implants were measured from the scans. A radiologic stent was prepared on the study model using three radiopaque pins per implant site, which simulated the implant in the CBCT scan. The pin which was in the direction of the residual bone was identified and retained, and the remaining pins were removed. The retained pin was utilized and the final surgical stent was prepared. It was checked if the final implant placement could be accomplished surgically using the modified stent. Results: A total of 7 implants were inserted. The final implant placement was based on the CBCT data and was evaluated by postoperative radiographs. All the implant sites showed proper placement of the implants. Conclusion: The stent used in our study was cost effective and easy to fabricate. Apart from the anteroposterior direction, it was also possible to give buccolingual direction to the implant, reducing the chances of perforation.